A Systematic Review of Tier 1 PBIS Implementation in Alternative Education Settings. (August 2021) - Grasley-Boy, Nicolette M.; Reichow, Brian; van Dijk, Wilhelmina; Gage, Nicholas
Positive Behavioral Interventions and Supports (PBIS) is a multitiered system of support for behavior used in many schools across the world. Researchers have begun adapting and evaluating Tier 1 of PBIS for students placed in alternative education (AE) settings. The purpose of this review is to synthesize these evaluations. We systematically searched two electronic databases to find potential studies of Tier 1 PBIS in AE settings. We screened 47 full texts, 19 of which met all inclusion criteria. Most studies (16 of 19, 84%) evaluated student behavioral outcomes, while seven studies (37%) evaluated academic outcomes alone or in addition to behavioral measures. Overall, restraints and seclusions generally decreased following Tier 1 implementation, but behavioral incident changes were variable and academic outcomes only improved for students enrolled continuously throughout the studies. The findings of this review support the need for continued evaluations of Tier 1 in AE settings using more rigorous methodologies and metrics that account for rolling admissions. The observed reductions in restraints and seclusions are promising for students and practitioners given the poor outcomes associated with these consequences.